Interlining Cr(VI) remediation mechanism by a novel bacterium Pseudomonas brenneri isolated from coalmine wastewater. (1st March 2019) - Banerjee, Soumya; Kamila, Biswajit; Barman, Sanghamitra; Joshi, S.R.; Mandal, Tamal; Halder, Gopinath
Abstract: A bioremedial approach was investigated on the removal of Cr(VI) from aqueous solution using a novel chromium reducing bacteria isolated from coalmine wastewater. Cr(VI) removal efficacy of the bacterium was determined in a series of batch studies under the influence of various parameters viz., pH (1–7), temperature (20–40 °C), initial metal concentration (1–150 mg/L), agitation speed (80–150 rpm) and substrate concentration (1–5 mg/L). Oxygen involvement in the removal process was determined by different incubation conditions. Substrate consumption and its resultant biomass generation were considered for determining the viability of the microbe under varied metal concentration. The microbial isolate survived in Cr(VI) tainted solution with initial concentration of 1–140 mg/L, among which maximum remediation was found in 60 mg/L Cr(VI) loaded solution. The bacterial species also survived in other metal solution viz., Fe(II), As(V), Cu(II), Pb(II), Zn(II), Mg(II), Mn(II) apart from Cr(VI). Multiple approaches were tested to facilitate understanding of the bacterial Cr(VI) removal mechanism. The bacteria accumulated metal ions in the exponential growth phase both on and within the cell. Underlying latent factors which governed the bacterial growth and its removal activity was determined with the classical Monod equation. The isolated bacterium also survived in the bimetallic solutions with significant removal of Cr(VI). The microbial species isolated from mining area was identified as Pseudomonas brenneri by 16s rRNA molecular characterization. Hence, the isolated novel bacterium illustrated promising involvement towards bio-treatment of Cr(VI) laden wastewater. Graphical abstract: Image 1 Highlights: Cr(VI) reducing bacterium was isolated from coalmine area. The isolate was identified as Pseudomonas brenneri by 16s rRNA characterization. The incubation condition parameters were optimized. Cr(VI) bioremediation efficiency was tested for both single and bimetallic solutions. Cr(VI) bioremedial process was substantiated with Monod's equation.